The ensuring low-income women have healthy children through the integrated PKH-posyandu-oral health program - Lestari, I Gusti Agung Ayu Pradipta (BKM Public Health and Community Medicine, 2021)
Pregnant women from underprivileged families (Gakin) who experience difficulties in fulfilling good nutritional intake for fetal growth and development, as stated in Gunungkidul Regent Regulation No.2 of 2020 concerning regional action plans to ensure low-income women can have children health through the integrated PKH-Posyandu-Dental and Oral Health program. The SRIKANDI NUSANTARA team (SeRIus to serve with dedicated to NUSANTARA which consists of the integration of PKH-Posyandu-Dental and Oral Health (dentists and dental hygienists)) is a team that results from the efforts of the local government to integrate existing programs so that can support each other, and coordinate proactively to plan, prepare, implement, and distribute food, brush, and toothpaste assistance for pregnant women who are recorded with the source of funds coming from the allocation of funds from BOK puskesmas, APBDes and also supported by PKH. The SRIKANDI NUSANTARA team can also train midwives related to standards of dental and oral health for pregnant women, empowerment of posyandu cadres in order to reactivate classes for pregnant women regularly to collaborate and train PKH officers to help monitor the oral and dental health of pregnant women. It is also important to monitor the health and nutritional status of the mother after childbirth or during breastfeeding and the development of babies and children. The SRIKANDI NUSANTARA team also had to fill in the maternal health status into a complete medical record. Information technology experts need to be provided to design information systems that can be accessed in an integrated manner, and use social media that can be accessed by the public to promote and educate about health. The SRIKANDI NUSANTARA team distributes medicines, vitamins, brushes and toothpaste as well as food assistance during pregnancy, in which case the head of the puskesmas needs to ensure that assistance is received by pregnant women. Pregnant women do not need to worry about health costs, and later deliveries because they are supported by the Maternity Insurance Program (Jampersal). The Regent as the highest stakeholder in the region needs to plan and decide to make policies and programs for pregnant women that are appropriate, effective, and efficient. Community groups can also be involved to actively participate in supporting policies and government programs that run transparently for the achievement of a goal, namely the creation of a healthy and beneficial future generation for the nation and state.